Application of elderly donor for liver transplantation - Li, Jiang (Int J Clin Exp Med, 2015)
Recently, much more attention has been paid on application of elderly donor due to the shortage of organs. Although liver quality of elderly donors may be sub-optimal comparing with that from younger donors, primary non-function of a liver graft is a rare event. On the other hand, long-term graft and recipient survival for usage of elderly grafts has become a major concern and focus of research. Many transplant centers have changed the upper limit of donor age from previous 50 to 70 or even 75-year-old and achieved good graft function. Although some scholars believed that liver transplant using elderly grafts was associated with high probability of delayed liver function recovery, graft loss and hepatitis C recurrence, reports from several transplant centers document that long-term survival of grafts and recipients may be significantly improved through certain screening of donors and recipients before transplant. In conclusion, it is very important and relatively safe to use grafts from elderly donors to expand the donor pool. However, elderly donors and corresponding recipients must be carefully selected before transplant. The long-term effect of advanced age on grafts and recipients need to be evaluated through a comprehensive and long-term in-depth observation.